Accidental Sampling Study on Quality of Life for Diabetes Mellitus Patients and Family Support System - Afnuhazi, Ridhyalla; Hendrawati, Hendrawati; Ahsan, Ahsan; Putri Andayani, Rifka; Purnamasari, Devi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
Family support is a major factor in maintaining metabolic control that will affect quality of life. The research objective was to determine the relationship between family support and quality of life for people with diabetes mellitus. This research is a cross sectional study using the Accidental Sampling method. It was conducted at the Puskesmas Kebun Sikolos with a total of 90 respondents. The statistical test used was chi-square. The results of statistical tests showed a relationship between family support and quality of life for people with diabetes mellitus with a value of p = 0.000 (<Î±0.05). So it can be concluded that there is a relationship between family support and quality of life for people with diabetes mellitus.